The controversial figure of “self-plagiarism” Would it be pertinent to regulate it legislatively in Peru? - Luna Rodríguez, Carlos Vladimir (2023)
“Self-plagiarism” is a figure provided in the academic and scientific field to describe the behavior of authors consisting of “plagiarizing themselves”, something that would occur when an author publishes a work whose content coincides with that of another work by the same author previously published, without citing the previous work. Unlike plagiarism, self-plagiarism is not regulated by law, it is only provided for by regulation through guidelines from scientific journals and educational institutions. In this regard, the possibility of legislatively regulating self-plagiarism within the copyright regulations is proposed in this paper, so that authors have a clear regulatory framework that facilitates their research and publication task.